Transprofessional education in the student discourse: Demand, expectations, risks - A. N. Pinchuk; S. G. Karepova; D. A. Tikhomirov (Образование и наука)
Introduction. Modern concepts of developing labour market and education defined in the digital economy paradigm, enunciate the imbalance between the rapidly changing requirements of the new economy and the system of vocational training. The nonlinearity of professional and educational trajectories brings to the fore, and the practice of continuous professional development and retraining becomes particularly important. Hence, special attention is drawn to the idea of transprofessional education, which reflects a new direction in future personnel labour market development. The prospects and possibilities of implementing the concept of transprofessionalism in the modern system of higher education require understanding a number of conceptual and practical issues, therefore, it seems urgent and timely to analyse the needs of students themselves in obtaining this type of education.Aim. The aim of the article was to analyse the demand for transprofessional education in the student discourse, as well as to articulate the actualised students’ expectations in the subjective assessments and risks associated with the spread of a new type of transprofessional specialists.Methodology and research methods. The authors relied on the concepts of pedagogy, sociology and economics of education that allowed them to study the educational demand of students for transprofessional education. The study was built within the framework of a multiple strategy based on the “filling in the gaps” approach proposed by E. Bell and A. Bryman. The source of empirical data was the results of a sociological study conducted in February–May 2021. At the first stage of the study, on the basis of a target sample, 1357 students, who are studying various educational programs of the social and humanitarian profile of the bachelor’s degree and master’s degree, were interviewed. The representation of the results of a quantitative study is based on a statistical analysis of the survey data using nonparametric methods to check the relationship between variables. The qualitative analysis of the essay texts was carried out within the framework of historical discourse analysis, which required the use of a three-dimensional analytical apparatus that allowed the authors to reveal the linguistic and constructive features of the construction of texts identify argumentation strategies and fix personal meanings in the content of the essay.Results and scientific novelty. The theoretical analysis carried out in the work allowed the authors to reveal the sociological component of the conceptualisation of the phenomenon of transprofessionalism, which consists in the aspect of the subjective interpretation of its content characteristics and the argumentation of the demand for new competencies. The educational demand of students for transprofessional education and the perception of transprofessionals in the labour market were empirically analysed. The survey showed that in most respondents’ opinions, the ability to go beyond a profession becomes one of the key characteristics of an in-demand specialist in modern conditions. Based on the texts of the essay, various ways of articulating personal positions in relation to the idea of transprofessionalism were identified; metaphors were presented that thematise transprofessional education in a particular context of understanding; expectations and risks explicated in the framework of subjective forecasting were studied. As the analysis of empirical materials has shown, the argumentation techniques of the majority of the study participants reflect the guidelines for the multidimensionality of professional competencies in the rapidly changing professional and labour sphere. At the same time, the students spoke most of all about the need for experience in mastering the related branches of specialisation. The desire to master another profession was much less frequent. It is important that most respondents experience going beyond their speciality as a necessary component of competencies in the modern world.Practical significance. The obtained results can be applied in pedagogical practice when planning educational trajectories of students, as well as used as informative material in further research related to the study of the development of the higher education system and the changing world of professions in a digital society.